1974
DOI: 10.1111/j.1365-2141.1974.tb00474.x
|View full text |Cite
|
Sign up to set email alerts
|

Separation and Partial Characterization of a Coagulant Enzyme from Bitis gabonica Venom

Abstract: Summary. The venom of the Gaboon viper (Bitis gabonica) has been shown to possess both coagulant and anticoagulant activities in vitro. These findings confirm in part previous results, the latter effect probably being achieved by proteolytic breakdown of fibrinogen.A partially purified coagulant has been recovered by ion‐exchange chromatography and gel filtration. Initial results indicate that this material may be similar in some respects to ancrod and reptilase. Anaesthetized rabbits were totally defibrinate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1978
1978
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Three serine protease containing fractions (E I to E III) isolated from B. gabonica venom have showed kinin releasing activity (E I), very low kinin releasing and high fibrinolytic activities (E II) and low clotting activity (E III) [10]. Marsh et al [26] reported two thrombin-like enzymes from B. gabonica venom, one with rapid defibrinating activity and another with a weak defibrinating activity. Some VVSPs from other snakes have been found to have two functions, for example crotalase has both kininogenase and fibrinogenolytic activities [22], and jararacussin [27], habu [28] and kangshuanmeni [29] are examples of serine proteases which have both α and β fibrinogenolytic activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three serine protease containing fractions (E I to E III) isolated from B. gabonica venom have showed kinin releasing activity (E I), very low kinin releasing and high fibrinolytic activities (E II) and low clotting activity (E III) [10]. Marsh et al [26] reported two thrombin-like enzymes from B. gabonica venom, one with rapid defibrinating activity and another with a weak defibrinating activity. Some VVSPs from other snakes have been found to have two functions, for example crotalase has both kininogenase and fibrinogenolytic activities [22], and jararacussin [27], habu [28] and kangshuanmeni [29] are examples of serine proteases which have both α and β fibrinogenolytic activities.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to understand that the effects of VVSPs occur in the context of the functional activities of other potent biological venom components including other serine proteases, metalloproteases and phospholipases. Marsh et al [26] reported that the venom of B. gabonica causes rapid defibrination together with widespread haemorrhage, cardiac and pulmonary damage. Rhinocerase does not catalyse plasma clot formation but hydrolyses fibrinogen.…”
Section: Discussionmentioning
confidence: 99%
“…The two independent lineages of giant Bitis are the most widespread and medically significant of the Bitis species due to their distribution, abundance in farmland, and extremely large venom yields. The most well studied species ( B. arietans , B. gabonica and B. rhinoceros ) have been studied in-depth due to the potent anticoagulant and hemorrhagic effects of their venom, being responsible for a significant proportion of the mortality and morbidity of snakebites in Africa [4,5,30,33,34]. The venom of both lineages of giant Bitis species causes a variety of effects including spontaneous and persistent bleeding, incoagulable blood, hemorrhage, hypotension and rapid defibrinogenation [30,31,32,33].…”
Section: Introductionmentioning
confidence: 99%
“…The characterization of the effects of rhinocetin on a range of collagen-induced (integrin α2β1-dependent) platelet functions such as inside-out signaling, calcium release, granule secretion, and thrombus formation greatly improves our understanding of this group of viper snaclecs. In a clinical context, rhinocetin inhibition of platelet function is consistent with the bleeding pathology that follows systemic envenoming by gaboon vipers (48). …”
Section: Discussionmentioning
confidence: 74%